E EFFECT OF CONCENTRATION OF STUDYING AT HOME ON STUDENTS LEARNING ACHIEVEMENT IN CLASS VIII DURING THE COVID-19 PANDEMIC AT SMP GKPS 3 PEMATANGSIANTAR - Marlindoaman Saragih; Risjunardi Damanik (Sean Institute, 2022)
This study was conducted to obtain an overview of the effect of concentration on studying at home on student achievement in class VIII during the Covid-19 Pandemic Period at SMP GKPS 3 Pematangsiantar. The results of this study indicate that students have high concentration. The average value of student learning achievement grade VIII SMP GKPS 3 Pematangsiantar is 83.50 . The correlation between the effect of learning concentration at home on learning achievement is 0.313, which means a high correlation. From the results of hypothesis testing on the t-test, it is obtained t-count = 6.673, and at the level of = 0.05 and df = 58 obtained t-table = 1, 67. So the price of t-count is greater than the price of t-table, so in this case Ha is accepted, meaning that there is an effect of concentration on studying at home on student achievement in class VIII during the Covid-19 pandemic at SMP GKPS 3 Pematangsiantar. From the results of the determination test, it was found that the contribution of concentration to study at home on student achievement in class VIII during the Covid-19 pandemic at SMP GKPS 3 Pematangsiantar was obtained. Based on the results of data processing, it was concluded that there was an effect of concentration on student achievement in SMP GKPS 3 Pematangsiantar even though the teaching and learning process was online.